1984
DOI: 10.2190/ayk2-qrj7-n8pu-m9b5
|View full text |Cite
|
Sign up to set email alerts
|

Who Volunteers for Adult Development Research?: Research Findings and Practical Steps to Reach Low Volunteering Groups

Abstract: The present study is an attempt to determine volunteering bias in racial, gender, and age groups in an adult development study. Samples were drawn from three different types of organizations in the Columbia, South Carolina SMSA. Volunteering rates were calculated as a function of the number eligible to participate in three age groups: 1) young adult (aged 20–25); 2) middle adult (aged 40–45); and 3) old (aged 60–80). The middle group volunteered at a higher rate than the other two age groups, but this effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…In contrast, the "45 and Up Study" (N = 36,645), launched 10 years later, reported a response rate of just 18% (to mailed invitations) [19]. Further, women may be more likely than men to volunteer as study participants, as are midaged adults compared with younger adults [178]. ADF personnel also differ from the general Australian population with regard to their high geographical mobility.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the "45 and Up Study" (N = 36,645), launched 10 years later, reported a response rate of just 18% (to mailed invitations) [19]. Further, women may be more likely than men to volunteer as study participants, as are midaged adults compared with younger adults [178]. ADF personnel also differ from the general Australian population with regard to their high geographical mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘female’ nature of the condition may also have influenced enthusiasm to participate in the present investigation as well as in GBE. In some types of research women are more likely than men to volunteer [42], and motivations of female research volunteers may differ from those of men [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The dominant status model developed by Lemon, Palisi, and Bennett-Sandler (1972) and further elaborated by D. H. Smith (1983Smith ( , 1994 would predict less participation for minorities because of their less prevalent social positions and roles within our sociocultural system. In general, most studies find that Whites do volunteer more than Blacks and Latinos (e.g., Bryant et al, 2003;Cannon, Higginbotham, & Leung, 1988;Gallagher, 1994;Sundeen, 1992;Todd et al, 1984); however, this often depends on whether bivariate or multivariate techniques are employed (D. H. Smith, 1994) or whether the individual was asked to volunteer (Bryant et al, 2003, Musick et al, 2000.…”
Section: Race and Giving And Volunteeringmentioning
confidence: 99%